2011
DOI: 10.1111/j.1447-0349.2010.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumers and carers as partners in mental health research: Reflections on the experience of two project teams in Victoria, Australia

Abstract: A successful working partnership in research between a consumer project team from the Victorian Mental Illness Awareness Council and a carer project team from the Victorian Mental Health Carers Network was forged during their collaborative involvement in an innovative 2-year pilot project funded by the Victorian Government of Australia. This project trialled new ways of capturing consumer and carer experiences of mental health services, and that feedback was integrated into service quality improvement. Towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…), which was highlighted by Callander et al . (), who found that decisions about methodology were made without involvement of user‐researchers. van Draanen et al .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…), which was highlighted by Callander et al . (), who found that decisions about methodology were made without involvement of user‐researchers. van Draanen et al .…”
Section: Resultsmentioning
confidence: 96%
“…In several studies, user‐researchers or potential user‐researchers had participated in research training (Callander et al . ; Croft et al . ; Gillard et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving toward more collaborative styles of care and more effectively meeting consumer needs in a holistic way will require system‐wide changes, including a nursing workforce ready for and receptive to consumer participation. Although there is research on staff views (McCann, Baird, Clark, & Lu, ) and that of consumer participants on the experience of consumer participation (Callander et al., ), there is a shortage of research on students' views and surveys of attitudes held by all those involved in mental health care.…”
Section: Introductionmentioning
confidence: 99%
“…Les personnes utilisatrices de services de santé mentale sont ainsi appelées à devenir des partenaires dans l'offre de services (50), par exemple en tant que pairs-aidants (51), des partenaires de recherche (52) et des partenaires d'enseignement (53). C'est ce dernier volet qui faisait principalement l'objet de cet article.…”
Section: Resultsunclassified